KECURANGAN LAPORAN KEUANGAN PADA PERBANKAN BEI: PENGARUH PERAN KOMITE AUDIT DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERIODE 2022-2024 - Siahaan, Irenita Fitri; Budiwitjaksono, Gideon Setyo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This study is driven by the persistent occurrence of fraud within the Indonesian banking sector. Such circumstances highlight the importance of implementing effective control strategies to prevent financial statement manipulation. Among the preventive efforts, enhancing the role of the audit committee and improving corporate social responsibility (CSR) disclosure are considered essential. Therefore, the purpose of this study is to assess the influence of the audit committee's performance and CSR disclosure on the prevention of financial statement fraud in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research employs a descriptive quantitative approach. The population consists of all banking institutions listed on the IDX between 2022 and 2024, totaling 47 companies. Using purposive sampling based on predetermined criteria, the final sample includes 20 companies. Data analysis was conducted through a series of instrument validity tests, classical assumption tests, and hypothesis testing, utilizing EViews version 12 as the analytical tool. The findings reveal that both the role of the audit committee and the level of CSR disclosure have a significantly positive effect on the prevention of financial statement fraud.